Body perfect - Streb, Kirk; Hayes, Bill; Wyk, Judy Van; Quattrone, Kathy; Grassie, John; Stozier, Henry (Discovery Channel, 2000)
This program tells the latest in cosmetic surgery. From ultrasonic liposuction to anatomical implants to a full body lift, Body Perfect travels the globe to profile patients and surgeons before, during and after their cosmetic procedures.